Desenvolvimento e validação de um diário miccional de fácil compreensão - Girão Neta, Odete Andrade Girão (2023)
Introduction: Lower Urinary Tract Symptoms (LUTS) are associated with abnormalities that occur during bladder storage. Among the available assistive technologies for evaluating these symptoms, the voiding diary stands out as a patient-centered, self-reported, non-invasive, and low-cost instrument. However, difficulties in understanding and interpreting the filling methods of the instrument are still observed, especially for patients with lower educational levels. Objective: Develop and validate a three-day bladder diary for Brazilian women. Methods: This is methodological research developed in three stages: literature review and development of the voiding diary; validation of content and appearance of the voiding diary by expert judges and validation of the voiding diary by the target audience regarding clarity and understanding for completion, and criterion validation by associating the data recorded in the diaries with data from the Questionnaire for Urinary Incontinence Diagnosis (QUID-Br). Expert professionals in urogynecology/women's health composed the sample of judges, and women with LUTS treated at two health centers formed the target audience. A questionnaire adapted from the Suitability Assessment of Materials (SAM) was used for validation with expert judges. For validation by the target audience, a structured evaluative questionnaire was used on the aspects of understanding, language, appearance, and use of the voiding diary. The data were analyzed according to the Content Validation Index (CVI), with a minimum of 0.78 for validation with experts, and based on agreement of at least 75% positive responses from the target audience. Criterion validity was analyzed using Kappa statistics and percentage agreement, with κ > 0.4 and agreement > 50% considered. Results: Seventeen experts validated the voiding diary. The overall CVI was 0.90. Among the domains, "Cultural Adequacy" was the best evaluated, with an average CVI of 1.0, followed by "Language," with an average CVI of 0.96. The domain with the lowest score was "Layout/Presentation," with an average CVI of 0.69. After suggested changes by the experts, the voiding diary was evaluated by 22 women. The items "Did you understand what you needed to write in the diary?" and "Are the illustrations adequate?" received maximum scores of 100%. The item "Do the font and size of the sentences allow for good reading?" achieved the lowest agreement score at 68%. However, the voiding diary achieved a level of agreement of 84.2% positive responses. The criterion test demonstrated good agreement between the questionnaire and the diary records for urge incontinence (k = 0.639; p<0.05; 81.8%) and reasonable agreement with weak correlation for stress incontinence (k = 0.271; p>0.05; 63.7%). Conclusion: The methodological process of elaboration and validation of the bladder diary allowed the construction of a valid instrument capable of identifying Lower Urinary Tract Symptoms. The elaboration of a bladder diary should take into account the specificities of the target audience associated with language factors and understanding of use, favoring the expansion and qualification of women's health care related to voiding dysfunctions at different levels of health care.